LEGAL REGIME OF INVESTMENTS OF INTERNATIONAL COMPANIES IN THE RUSSIAN FEDERATION - T. F. Gadzhiev (Гуманитарные и юридические исследования, 2021)
The article discusses the peculiarities of legal regulation of investment activities of international companies that are members of special administrative regions. The relevance of this problem is determined by the need for increasing the investment attractiveness of the national economy, in such ways as improving the legal regulation of investments made by corporations with the status of international companies on the territory of Russia.The goals of creating an investment-friendly environment have found their legal basis in the creation of special administrative regions. The achievement of these goals is inextricably linked with the establishment of a competitive legal investment regime for residents of special administrative regions called international companies. The novelty of the Institute of international companies and its «exoticism» for the Russian legal system determined the scientific interest in the problems of legal regulation of their investments.The article compares the legal regime of investment activities of participants in special administrative regions and residents of other special economic zones on the territory of the Russian Federation, and highlights the difference in the territorial nature of investments due to the targeted nature of the rules on international companies. The author draws attention to the problem of mixing different legal regimes for investment activities on the territory of the special administrative region on Russky island and related issues of competition legal norms.The article also analyzes the problem of discrepancy between the size of investments of international companies and public expenditures related to the creation and operation of special administrative regions. In this regard, the author justifies the need to establish an annual registration fee for international companies in the tax legislation as soon as possible. Fixing this type of fee will give the opportunity to compensate for the part of the budget expenditures on the creation of infrastructure for special administrative regions.